Biodegradable Peptide–Silica Nanodonuts. Issue 11 (16th February 2016) - Maggini, Laura; Travaglini, Leana; Cabrera, Ingrid; Castro‐Hartmann, Pablo; De Cola, Luisa
Abstract: We report hybrid organosilica toroidal particles containing a short peptide sequence as the organic component of the hybrid systems. Once internalised in cancer cells, the presence of the peptide allows for interaction with peptidase enzymes, which attack the nanocarrier effectively triggering its structural breakdown. Moreover, these biodegradable nanovectors are characterised by high cellular uptake and exocytosis, showing great potential as biodegradable drug carriers. To demonstrate this feature, doxorubicin was employed and its delivery in HeLa cells investigated. Abstract : Breakable nanodonuts : Hybrid organosilica toroidal particles (see figure) containing a short peptide sequence as the organic component are reported. Once internalised in cancer cells, peptidase enzymes attack the nanocarriers effectively triggering their structural breakdown. These biodegradable nanovectors are also characterised by high cellular uptake and exocytosis, and therefore they have been challenged as biodegradable drug carriers.